MAKE LINKIN PARK SITE USING MACROMEDIA FLASH 5.0 - Ilham Habibi; Ristyawati, SKom, MMSI Ristyawati, SKom, MMSI (Jurnal Sistem Informasi, 2004)
Today was a lot of software that is used for the manufacture of a biased website butfor the ordinary use of the software that a user must have expertise in a particularprogramming language. But the other is with flash, this software allows one to makethe homepage without the need for HTML proficiency or collect books. In addition tothe flash users can create good visual effects, and can produce a highly interactivewebsite.The concept of the site is expected to help internet users to make it easier to get thelatest news and information. And also the media to the site owner to deliver the newsand information related to the group band Linkin Park to its loyal fans in Indonesia.